La représentation de l’étranger dans le discours des habitants de Mostaganem - Abdelnour Benazzouz (Multilinguales)
This article deals with the figure of the “foreigner” in the speech of the inhabitants of Mostaganem, a city of the Algerian west coast. Based on three surveys conducted at different periods of time and on different audiences of speakers/inhabitants, we first identified the designations that refer explicitly to the inhabitant of the city perceived as "foreigner". Next, in a second phase, we were interested in the criteria of division (necessarily subjective) put forward and / or signified in the speakers’ answers. The conclusions point to a strong social anchoring of the "putting into words" of the other, through its stigmatization. Beyond the process of nomination, they also reveal the complexity of social reality, which raises the question of the process of urbanization in general and that of the Algerian cities in particular.